Analysis of Teacher Professional Commitment with Self-Efficacy and Digital Literacy Perfective - Murniarti, Erni; Sihotang, Hotmaulina (Advances in Social Sciences Research Journal, 2024)
This study aims to investigate the effect of digital literacy and self-efficacy on the commitment of the teaching profession at the Pangudi Luhur Foundation Jakarta. Teachers have an important role in educating, guiding, and assessing learners at various levels of education. The teacher qualification standards stipulated by Law No. 14/2005 emphasize the importance of pedagogic, personality, social, and professional competencies in carrying out their duties. The commitment of the teaching profession greatly affects the effectiveness of the learning process, while digital literacy and self-efficacy are internal factors that influence this commitment. The research method used was quantitative using Likert scale questionnaires. The research sample consisted of 104 teachers at Yayasan Pangudi Luhur Jakarta. The results showed that digital literacy had a positive and significant influence on the commitment of the teaching profession, with a regression of 0.909 and a determination of variance of 0.827. Similarly, teacher self-efficacy also had a significant influence on professional commitment, with a regression of 0.828 and a determination of variance of 0.686. However, when digital literacy and self-efficacy were considered together, the effect became stronger with a regression of 0.926 and a determination of variance of 0.858. These findings provide important implications for education practitioners, school principals, and educational foundations in developing strategies to increase the commitment of the teaching profession. Suggestions include organizing workshops and seminars to improve teachers’ digital literacy and self-efficacy, as well as support from school principals and foundations in this regard. Thus, this research makes a significant contribution in understanding the factors that influence the commitment of the teaching profession and provides a foundation for the development of more effective education in the future.